Thorahcic SMARCA4-deficient undifferentiated tumors with ganglioneuroma and enchondroma: implications for SLC7A11 and ARID1A expression: a case report - Yusuke Kito; Keisuke Kawashima; Chiemi Saigo; Masayoshi Hasegawa; Shusuke Nomura; Takuya Mikamo; Yuki Hanamatsu; Yasuhiro Matsuo; Tamostu Takeuchi (BMC, 2022)
Abstract Background SWI/SNF-related, matrix-associated, actin-dependent regulator of chromatin, subfamily A, member 4-deficient thoracic sarcoma (SMARCA4-DTS) is a rare disease that has recently been described as an entity. It is characterized by an aggressive clinical course and specific genetic alterations. As an immunohistological feature, the tumors are deficient in SMARCA4 and SMARCA2 and express sex-determining region Y (SRY)-box 2 (SOX2). Occasionally, there are cases that are less frequent and difficult to distinguish from SMARCA4-deficient non-small cell lung carcinoma (SMARCA4-dNSCLC). Therefore, the 5th edition of the World Health Organization (WHO) classification describes thoracic SMARCA 4-deficient undifferentiated tumors (SMARCA4-UT). In contrast, Carney's triad is a syndrome that combines three rare soft tissue tumors: gastric leiomyosarcoma, pulmonary chondroma, and extra-adrenal paraganglioma. Protein kinase cAMP-dependent type I regulatory subunit alpha (PRKAR1A) has been proposed as the causative gene. Both diseases are valuable cases; moreover, there have been no previous reports of their coexistence. Case presentation A 43-year-old man visited our hospital because of respiratory distress. Computed tomography revealed a large mass measuring 55 mm in the upper lobe of the right lung and front mediastinum, with metastases in the surrounding lymph nodes. Needle biopsy was performed for diagnosis, and histological examination of the samples revealed monotonous epithelioid-like cells with loose binding and sheet-form proliferation. The tumor cells had distinct nuclei with some rhabdoid-like cells. Immunohistochemical analysis revealed that the tumor cells were positive for AE1AE3, SOX2, CD34, and p53 and negative for SMARCA4 and SMARCA2. The patient died 6 months after admission, without any treatment. Autopsy revealed ganglioneuroma and enchondroma suggestive of an incomplete Carney complex. Conclusion SMARCA4-UT is a rare and recently established disease. While it is difficult to diagnose, it is necessary to distinguish undifferentiated carcinoma, large cell carcinoma, Ewing sarcoma, and epithelioid sarcoma when diagnosing tumors involving the mediastinum. Moreover, cases of SMARCA4-UT with ganglioneuroma and enchondroma are very rare. We discuss and report a case of SMARCA4-UT in which we also examined ARID1A and SLC7A11expression.